(untitled) (Diametros, 2015)
This comment on Professor ter Meulen’s paper, "Solidarity and Justice in Health Care," offers additional perspectives on solidarity’s importance for health. Noting the findings of social epidemiology, the paper explains that health has important public good dimensions. It is both non-rivlalrous because one person’s health does not diminish another’s, and it is largely determined by non-excludable access goods, including social networks, social determinants, and public health efforts. The public good dimension of health underscores the mutual dependence and shared stake that people have with respect to health, and highlights the importance of coming together in solidarity for the sake of health. This is not to say that solidarity cannot also foster exclusionary tendencies; however, the recognition of mutual dependency with respect to health can foster an inclusive solidarity for the health of all people.